Comparison of screening tests with urine culture in urinary tract infection - K.L, Shobha; Rao, Amita; K, Shilpa; L, Ramachandra (International Journal of Medicine, 2014)
Introduction: Urinary tract infection (UTI) is an important health care problem affecting millions every year. Evaluation of suspected UTI includes history, physical examination and laboratory investigations. Urine analysis for presence of pus cells, bacteria and culture are important in the adequate management of UTIs. Aim of the study was to analyze the screening tests with culture method in the diagnosis of UTI. Materials and methods: 100 turbid midstream urine specimens collected in a sterile wide mouthed container were included in the study. Mid-stream urine specimens collected from both inpatients and outpatients attending a tertiary care hospital were included in the study. Urine specimen was subjected to Gram’s staining and catalase tests and inoculated into culture medium. Semi-quantitative culture technique was followed. Organisms were identified for significant bacteriuria. Results: Samples collected from 40 years of age and from patients more than 40 years of age were 64% and 51% were male patients. Gram’s stain showed 59% of samples with organisms. Pus cells were seen in 54% of the smears and all the samples had significant growth in the medium Catalase positive was 53%, all the 53 strains had growth on culture plate. E. coli was the commonest organism isolated on the culture plate. Thus screening tests like Gram’s stain, pus cells detection and catalase test can be used as a rapid method to detect urinary tract infection and to start the antibiotic therapy though culture remains the gold standard method for detection of urinary tract infection. Keywords: Gram’s Staining, Pus Cells, Catalase Test, Culture Medium, Significant Bacteriuria.